Enhancing School Principals' Discipline Character through Transformational Leadership Training in Praya District - Raden Sumiadi; Syahrir Syahrir; Supriadin Supriadin; Adi Purmanto (Abdi Masyarakat, 2026)
Principals are educational leaders who play a crucial role in building an effective, professional, and character-based work culture within the school environment. One of the characteristics that principals need to possess and strengthen is discipline, as this character influences the quality of school management, teacher performance, and the achievement of educational goals. However, various challenges in school management, such as suboptimal time management, consistent program implementation, and oversight of task implementation, indicate the need for efforts to strengthen the disciplined character of principals. One strategy that can be implemented is through transformational leadership training oriented towards increasing leadership capacity, exemplary behavior, motivation, and commitment to change. This activity aims to improve the understanding and ability of principals in applying the principles of transformational leadership as a means of strengthening the character of discipline. The training was conducted through a participatory approach that included material delivery, group discussions, case studies, self-reflection, and the development of follow-up plans. Participants were principals in Praya District who were from elementary school education levels. The results of this activity were an increased understanding of the concept of transformational leadership, a growing awareness of the importance of discipline as a core leadership value, and an increased ability to manage time, implement school programs consistently, and serve as role models for the school community. Furthermore, this activity can also encourage the development of a sustainable culture of discipline within the school environment through inspirational leadership practices oriented toward positive change.